PENGEMBANGAN SIKAP TOLERANSI SANTRI PONDOK PESANTREN AL-KAUTSAR MELALUI PENDIDIKAN ISLAM MULTIKULTURAL - Moh. Afnan Rahmaturrahman; Suryanto (LP2M IAI Miftahul Ulum Pamekasan, 2022)
This research aims at analysing the implementation of multicultural education toward santri's tolerant attitude development. This study employs descriptive qualitative method which covers the process of data collection through in depth interview, which later be analysed by data reduction and categorisation according to its critical themes as narrated in the report. This research reveals that the implementation of multicultural education in Pondok Pesantren Al-Kautsar is motivated by (i) the principle of Tawassuth, Tawazun,I'tidal, and Tasamuh, (ii) Tanbih Thariqah Qadiriyyah wa al-Naqsyabandiyyah Suryalaya, and (iii) five fundamentals in maqashid al-Syari'ah. In addition to the development of santri's tolerant behaviour, the school curriculum at the Pondok Pesantren Al-Kautsar is integrally designed containing multicultural education concept.